2021
DOI: 10.1002/pmrj.12539
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Irregularity, Hormonal Contraceptive Use, and Bone Stress Injuries in Collegiate Female Athletes in the United States

Abstract: Background Menstrual irregularity (MI) is common in female athletes and is a component of the Female Athlete Triad (Triad). Many athletes with the Triad are started on hormonal contraceptives (HC) for MI, but this interferes with the ability to monitor menstrual cycle regularity and can mask other causes of MI. There are limited studies investigating the relationship between MI, HC use, and injury in female collegiate athletes. Objective To examine the prevalence of and relationship between HC use, MI, and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
(123 reference statements)
0
18
0
Order By: Relevance
“…Following volunteer service, some lost BMD may have been recovered. Volunteers' study period (2.6%) and lifetime (11%) stress fractures rates were lower than reported among athletes (4.6-25%) [12,37,38]. Athletes may be at higher risk for stress fracture due to more intense physical activity and a longer duration of SA compared to volunteers.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Following volunteer service, some lost BMD may have been recovered. Volunteers' study period (2.6%) and lifetime (11%) stress fractures rates were lower than reported among athletes (4.6-25%) [12,37,38]. Athletes may be at higher risk for stress fracture due to more intense physical activity and a longer duration of SA compared to volunteers.…”
Section: Discussionmentioning
confidence: 76%
“…The Triad occurs in female high school, collegiate, and elite athletes [6,7]. In collegiate athletes, Triad components have the following prevalence estimates: Low EA (11.8-67%) [8,9], MI (16-36%) [8,[10][11][12][13], and low BMD (Z-score < −1) (1-3.5%) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Between 20 and 70% of elite female athletes use hormonal contraception, with a significant variation depending on the country (Australia, Denmark, Norway, Sweden, United States) and the sports discipline (football, basketball, track and field…) [ 7 , 9 , 10 , 11 ]. A large majority (68–75%) of these athletes take second-generation combined estrogen-progestin oral contraceptives (COCs), rather than progestin-only contraceptives (20–30%) [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Progestin-only contraception is used continuously, either in tablet form or with an intrauterine device (IUD), and the main progestins are levonorgestrel and desogestrel. A significant number of elite athletes use hormonal contraception primarily to regulate their MC (24%), particularly those with a history of menstrual disturbances [ 9 ]. Moreover, a majority of COC users report having deliberately manipulated timing, frequency, and amount of menstrual bleeding, with a prevalence of 60–77% among competitive athletes, who most often cited special events and holidays, convenience, and sports competition as the reasons [ 7 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many elite female athletes use hormonal contraception, with figures varying from 20% to 70% depending on the country and sport [ 18 , 19 , 20 , 21 ]. However, little is known about the impact and prevalence of HC use and the effects of intermittent treatment.…”
Section: Introductionmentioning
confidence: 99%